Effect of Nitrogen Source and Management on Ammonia Volatilization Losses From Flooded Rice-Soil Systems - Vlek, P.L.G.; Craswell, E.T. (Wiley, 1979)
Ammonia volatilization was studied by equipping capped greenhouse pots with a forced‐draft system with external acid trap or by placement of open pots in a closed gas‐lysimeter (allowing plant growth) with internal acid traps. In both systems air turbulence was optimized to simulate undisturbed open systems. Flooded soils were fertilized with approximately 50 or 100 kg N/ha of granular urea (GU), ammonium sulfate (AS), and two modified urea products—sulfur‐coated urea (SCU) and urea supergranule (USG). The first three materials were broadcast and incorporated, whereas the last was placed at a depth of 8 cm.Ammonia volatilization from urea proceeded rapidly following hydrolysis of urea in the floodwater, leading to losses of up to 50% of the applied urea within 2 to 3 weeks. Ammonia loss from (NH4)2SO4 occurred to a lesser extent due to a lack of alkalinity and occurred at a nearly constant rate, accumulating to ∼15% loss in 3 weeks. Ammonia losses from the modified urea materials were negligible.Soil pH had little effect on the pH of the floodwater and, thus, on the ammonia volatilization process. However, ammonia volatilization losses were generally reduced by factors that reduced the level of ammoniacal N in the floodwater, such as increasing soil CEC and reduced N application.Daily ammonia volatilization losses correlated well (r = 0.92) with the NH3(aq) concentration of the floodwater sampled between 1000 and 1100 hours each day. This observation holds promise for the development of a simple technique for assessing ammonia volatization losses from flooded soils based on simple physical and chemical parameters of the floodwater.